PENINGKATAN KEMAMPUAN SISWA DALAM MENULIS TEKS BERITA DENGAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN MEDIA TEKS BERITA - Nur Ulfa (Universitas Wijaya Kusuma Surabaya, 2022)
The Problem Based Learning using ficture can be used to improve the ability to write short stories because these models, strategies, and media provide students whith idiom to find and start short story writing activities. The activity of writing short stories in the process of good practice by author has shown an increase in the ability to write short stories. The improvement in the ability to write short stories made by student can be seen from the increase in the enthusias tic learning process and the work in the form of write short stories